1995
DOI: 10.1002/hep.1840220113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ursodeoxycholic acid and chenodeoxycholic acid on human hepatocytes in primary culture

Abstract: Hepatic bile acid concentrations are elevated in chronic cholestasis because of reduced canalicular excretion and active ileal absorption of the fraction eliminated in the gut. Ursodeoxycholic acid (UDCA) reduces the intestinal absorption of endogenous bile acids, thereby diminishing the concentrations to which liver cells are exposed. In the isolated perfused liver (in which vectorial bile acid transport is maintained), UDCA reduces the cytotoxic and cholestatic effects of endogenous bile acids. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, it has been recently reported that, in cultured human hepatocytes, UDCA has no direct cytoprotective effect, which further supports that its effect is on the hepatocyte transport system. 23 The most particular effect of THDCA was the selective increase in PL secretion, even during coinfusion with TCDCA; the hepatic bile produced was more enriched in PL as compared with TUDCA or the saline control (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, it has been recently reported that, in cultured human hepatocytes, UDCA has no direct cytoprotective effect, which further supports that its effect is on the hepatocyte transport system. 23 The most particular effect of THDCA was the selective increase in PL secretion, even during coinfusion with TCDCA; the hepatic bile produced was more enriched in PL as compared with TUDCA or the saline control (P Ͻ .001).…”
Section: Discussionmentioning
confidence: 94%
“…More hydrophobic bile acids (CA, CDCA, DCA) rapidly induce apoptosis, whereas less hydrophobic bile acids (UDCA) are less toxic . Moreover, total plasma bile acids and primary plasma bile acids (CA and CDCA) levels have been shown to positively correlated with the AH severity and steatosis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have emphasized the cytoprotective effects of TUDCA in hepatocytes as the primary therapeutic mechanism in chronic liver disease. 44,45 The proliferating cholangiocytes may be an important promoter for liver injury after BDL 46,47 and play a role in the progression of chronic cholestatic liver diseases such as PBC. Because proliferating cholangiocytes release proinflammatory cytokines, 46,47 inhibition of cholangiocyte proliferation by UDCA and TUDCA may reduce cytokineinduced hepatic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%